Enhanced barrier, mechanical and viscoelastic properties of graphene oxide embedded glass fibre/epoxy composite for marine applications. (25th January 2021) - Anand, Abhijeet; Ghosh, Sohan Kumar; Fulmali, Abhinav Omprakash; Prusty, Rajesh Kumar
Graphical abstract: Highlights: Properties enhancement for marine application is achieved using Graphene Oxide. Study of water absorption kinetics has been done. Presence of cations leads to cross linking owing to lower properties degradation. Desorption of water saturated composite leads to recovery of viscoelastic properties. Abstract: The long-term performance of nano-modified glass fibre/epoxy (GE) composite in sea water has been an active area of research in the recent years but still requires better understanding of their environmental durability and reliability for various applications. This article aimed at reaping the two major benefits of graphene oxide (GO) i.e. cost and interfacial compatibility with epoxy matrix, to improve the barrier, mechanical and thermo-mechanical performance of GE composite in marine environment. In this investigation, GO modified GE (GO-GE) composites were subjected to 9 months of ageing in sea water and distilled water (for baseline measurement), both maintained at 15 °C, which is close to the average ocean surface temperature. Water uptake kinetics of the composite specimens was monitored using gravimetric analysis while the effect of water ingression on their flexural and thermo-mechanical behaviour was analysed in different ageing regimes, till saturation. Desorption of the water saturated composites was also carried out. Experimental results revealed that GO greatly impedes the sorption of water through the interfaces as the equilibrium water contents of 0.5% GO-GE composite were 36.3% and 25.4% lower than neat GE composite aged in distilled water and sea water respectively. Water saturated GO-GE composites also exhibited superior mechanical properties in comparison to saturated neat GE. Moreover, the salinity of sea water was found to have a beneficial impact on the aforementioned characteristics of GO-GE composites despite suppressing their barrier tendency. Fractography was conducted to comprehend and confirm the fundamental micro-mechanisms governing the experimental results obtained during different ageing regimes.